(untitled) (De la Crítica, 2023)
The present research work aims to analyze the transfer process (as a natural linguistic phenomenon) of the students of English business III of the Business Development Program of the Churugara Academic Complex in the reading and translation of Technical Texts Exhibition of Spanish to English to English as a foreign language. It is framed in a clear investigation of the descriptive type and that due to its particular characteristics, the design used is field. In order to obtain the necessary data, two (2) instruments of the survey model were applied to 15 students of the Business Development Specialty of this institution, all students of the English Curricular Unit Business III and who have in common have approved the subjects Business and English English II. First, they were applied a questionnaire formed by fifteen (10) periodicity items with two (2) response options (yes) or (no), each oriented to measure relevant aspects for the investigation and then, a test was applied of knowledge that consisted of two (2) parts, plus an exhibition text and that he intended for the student to incorporate into his memory the knowledge acquired in his academic training. The results obtained show that while most of them use reading and translation strategies according to their linguistic competence, that same majority shows a series of weaknesses related to negative transfer processes from the point of view of the lower levels of reading comprehension; And consequently, they have weaknesses when it comes to critically understanding the most relevant aspects of an exhibition technical text.